(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2023)
Nepal through the Ages: Reviving Ancient and Medieval Culture and Architecture: A Painting Exhibition of the Complete Works of Senior Artist, Hari Prasad Sharma organized by Nepal Heritage Society, Himal Association and Social Science Baha on September 6 – 26, 2019 at Nepal Art Council, Baber Mahal